SMART CITY: A NEW DEVELOPMENT TO INDIA (International Journal of Engineering Sciences & Management Research, 2015)
Smart cities optimize the use of technology in the design and operation of infrastructure and buildings in a way which meets the current and future needs of their citizens. To be truly ‘smart’ they also require consideration of governance and growth, urban development and infrastructure, the environment and natural resources, society and community. Physical digital integration of infrastructure will be of utmost importance for the success and survival of the next generation of cities. From mandating the construction of energy efficient buildings to create intelligent networks, cities are seeking to become “smarter